The success of tubularized-incised plate urethroplasty in adults and children - Polat, Haci (Springerplus, 2016)
PURPOSE: Hypospadias repair is rarely performed in adults. It is believed that the success rate is lower in adulthood. We aimed to compare the success rate of primary hypospadias repair with tubularized-incised plate (TIP) urethroplasty in adults and children. PATIENTS AND METHODS: The databases of consecutive boys and adults who were treated with TIP urethroplasty for primary hypospadias between 2012 and 2015 were evaluated. All operations in the boys and adult patients were performed by a single surgeon. We considered urethroplasty complications to include a urethrocutaneous fistula, neourethral stricture, meatal stenosis, diverticulum, and glans dehiscence. Urine flow was also evaluated using uroflowmetry. RESULTS: Seventy-seven consecutive patients underwent surgery by a single surgeon in the last 3 years for hypospadias repair. Nineteen of these patients were adults. Urethrocutaneous fistulae developed in 2 of the 19 (10.5 %) adults, and 3 of the 58 (5.2 %) boys. In addition, there were urinary tract infections in 2 (3.4 %) children, meatal stenosis in 1 (1.7 %) child, and glans dehiscence in 1 (5.3 %) adult. Uroflowmetry was normal in all patients. There was no difference in outcomes between boys and adults. CONCLUSION: Our data showed that the success rate of hypospadias repair with TIP urethroplasty is similar in adults and children. TIP urethroplasty is associated with good results in adults and boys.